MB-System - Final Report - Frans Veigar Garðarsson 1989-; Finnur Kolbeinsson 1989-; Jón Rúnar Arnarsson 1989-; Ólína Björg Þorsteinsdóttir 1973- (2012)
Heildatexti í lokaskýrslu. Prentuð útgáfu og öll fylgiskjöl eru varðveitt á CD á bókasafninu. For a parent who wants to register their children to activities there can be many complications. In most cases the parents must drive down to the sports club facilities, register their children and are possibly asked to show up later to pay. Being able to register and pay for their children online saves both time and money and should be considered a natural thing more than a necessity. Sport clubs have issues managing children registrations and payments for activities. Up until now this is mostly managed in various Excel documents which are hard to contain and can grow out of proportion. Having a system that monitors all registrations and payments helps sport clubs manage their participant’s registrations as well as giving them better insight and overview of the clubs finance. Mentor had a vision to create a system that would allow sport clubs to offer their activities to parents also allowing parents to register and pay for their children activities online. Mentor has worked with schools on solutions for several years and wanted to expand their customer base with this solution. This vision was proposed as a BSc final project in collaboration with Reykjavík University School of Computer Science. In this report we introduce our solution, MB-System that solves the problems addressed above. MB-System will allow parents to sign their children up for activities and pay for them online. Not having to go through the process of making a call, drive down to the sport clubs facilities and find the appropriate person will save time and make the whole process more effective. For sport clubs MB-System helps clubs keep track of members in various sports and give information and statistic about payments. Our solution enables accountants to register children for activities that have not already been registered by parents. MB-System also makes it possible to follow whether the activities have been paid for or not and export these ...